Implementasi Program Pengembangan Keprofesian Berkelanjutan Guru melalui Peningkatan Kompetensi Pembelajaran Berbasis Zonasi - Warni Tune Sumar; Sartje Tune Sumar (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2020)
Continuing professional development for teachers is a government policy in the context of improving the quality of education, through improving the quality of teachers. One of the activities in continuing professional development is teacher training. Teacher professional development activities can be carried out in three forms, namely personal development (including functional training and teacher collective activities), scientific publications, and development. To provide opportunities for teachers to participate and prepare themselves to experience change. Learning Competency Improvement Program is a program that aims to improve student competency through teacher training in planning, implementing, and evaluating learning that is oriented to higher-order thinking skills (HOTS). This program is part of the Continuing Professional Development program mandated by Law Number 14 of 2005 concerning Teachers and Lecturers and Minister of Administrative Reform and Bureaucracy Reform Number 16 of 2009 concerning the Position of Teacher Functionality and Credit Numbers. The zone to improve learning competence is basically part of a strategy to accelerate the development of equitable, quality and equitable education (Integration Development), through the management of teacher activity centers, teacher working groups, deliberations for subject teachers, and Teacher Guidance and Counseling Consultations, which has been done through Clusters or Rayon, especially in improving learning competence.